Banff 2019 Meeting Report: Molecular diagnostics in solid organ transplantation–Consensus for the Banff Human Organ Transplant (B‐HOT) gene panel and open source multicenter validation. Issue 9 (27th June 2020) - Mengel, Michael; Loupy, Alexandre; Haas, Mark; Roufosse, Candice; Naesens, Maarten; Akalin, Enver; Clahsen‐van Groningen, Marian C.; Dagobert, Jessy; Demetris, Anthony J.; Duong van Huyen, Jean‐Paul; Gueguen, Juliette; Issa, Fadi; et al.
Abstract : This meeting report from the XV Banff conference describes the creation of a multiorgan transplant gene panel by the Banff Molecular Diagnostics Working Group (MDWG). This Banff Human Organ Transplant (B‐HOT) panel is the culmination of previous work by the MDWG to identify a broadly useful gene panel based on whole transcriptome technology. A data‐driven process distilled a gene list from peer‐reviewed comprehensive microarray studies that discovered and validated their use in kidney, liver, heart, and lung transplant biopsies. These were supplemented by genes that define relevant cellular pathways and cell types plus 12 reference genes used for normalization. The 770 gene B‐HOT panel includes the most pertinent genes related to rejection, tolerance, viral infections, and innate and adaptive immune responses. This commercially available panel uses the NanoString platform, which can quantitate transcripts from formalin‐fixed paraffin‐embedded samples. The B‐HOT panel will facilitate multicenter collaborative clinical research using archival samples and permit the development of an open source large database of standardized analyses, thereby expediting clinical validation studies. The MDWG believes that a pathogenesis and pathway based molecular approach will be valuable for investigators and promote therapeutic decision‐making and clinical trials. Abstract : This Banff meeting report summarizes the progress of the Banff Molecular Diagnostics Working Group, which generated consensus on a transplant‐specific discovery gene panel and a potential roadmap for its validation for diagnostic application.